Preparation method of all-solid-state battery negative electrode material

By grinding red phosphorus and nanosilicon with cyclodextrin balls, forming a phosphorus-silicon composite material and reacting in a polychlorinated chloride solution, the problem of low specific capacity and volume changes of lithium-ion battery negative electrode material is solved, and a higher energy density is achieved and Cycle life.

CN119133424AActive Publication Date: 2024-12-13GUIZHOU MATERIAL IND TECH INSTITUE

Patent Information

Application Number
CN202411226369.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The commercial graphite negative electrode materials in existing lithium-ion batteries have lower specific capacity, and silicon-based materials have large volume changes and poor conductivity during the circulation process, which limits the improvement of the energy and cycle life of lithium-ion batteries.

Method used

A mixture of red phosphorus and nano-silicon is used to grind with cyclodextrin balls to form a phosphorus-silicon composite material, and react it in a polyacyl chloride solution. It is bound and encapsulated through the hollow structure of cyclodextrin to limit the expansion and diffusion of the negative electrode.

Benefits of technology

The specific capacity and cycle stability of the negative electrode material of lithium-ion battery are improved, and the energy density and cycle life of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of an all-solid-state battery negative electrode material, and belongs to the technical field of negative electrode materials, the method comprises the following steps: firstly, weighing a certain mass of red phosphorus and nano silicon, and carrying out ball milling and mixing to obtain a mixture; then carrying out ball-milling mixing on the mixture and cyclodextrin to obtain a phosphorus-silicon composite material; and finally, putting the phosphorus-silicon composite material into a polyacyl chloride solution to react for a period of time, and treating to obtain the all-solid-state battery negative electrode material. According to the invention, the cyclodextrin coated with the phosphorus-silicon mixture reacts with the poly-acyl chloride solution, and the phosphorus-silicon composite material is further encapsulated in the molecular cavity, so that phosphorus and silicon are prevented from diffusing out of the molecular cavity under the action of pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a method for preparing a negative electrode material for an all-solid-state battery. Background Art

[0002] Lithium-ion batteries have a series of advantages such as high specific capacity, stable operating voltage, good safety, and no memory effect, so they are widely used in many portable electronic instruments and equipment. With the rapid development of various electronic devices and electric vehicles, people have higher and higher requirements for the energy and cycle life of lithium-ion batteries. The negative electrode material is an important component of the battery. Together with the positive electrode material, it determines the key performance of the lithium-ion battery such as cycle life, capacity and safety, and has become a key research object.

[0003] Currently, the specific capacity of commercial graphite-based negative electrode materials is low, only 372mAh / g, which limits the improvement of the overall capacity of lithium-ion batteries and can no longer meet market demand. Silicon materials have been proven to be an excellent alternative to graphite materials for high-energy lithium-ion batteries because they have excellent theoretical specific capacity of up to 4200mAh / g. However, there are still some difficulties in the popularization of silicon-based materials, such as the large volume changes during the cycle and the poor conductivity of silicon materials themselves. These defects have seriously hindered the application of silicon-based materials in lithium-ion batteries.

[0004] Therefore, it is urgent to propose a method for preparing all-solid-state battery negative electrode materials to solve the above problems. Summary of the invention

[0005] The present invention discloses a method for preparing an all-solid-state battery negative electrode material, which can effectively solve at least one technical problem involved in the background technology.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A method for preparing an all-solid-state battery negative electrode material comprises the following steps:

[0008] Step S1, weighing a certain mass of red phosphorus and nano-silicon and mixing them by ball milling to obtain a mixture;

[0009] Step S2, mixing the mixture with cyclodextrin by ball milling to obtain a phosphorus-silicon composite material;

[0010] Step S3, placing the phosphorus silicon composite material into a polyacyl chloride solution to react for a period of time, and then treating it to obtain an all-solid-state battery negative electrode material.

[0011] As a preferred improvement of the present invention, the mass ratio of the red phosphorus to the nano-silicon is 5-8:5-2.

[0012] As a preferred improvement of the present invention, the mass proportion of cyclodextrin in the phosphorus silicon composite material is 0.5-5%.

[0013] As a preferred improvement of the present invention, in steps S1 and S2, the ball milling mixing rate is 200-500 rpm, the ball milling time is 15-60 min, and the ball-to-material ratio is 1:20-40.

[0014] As a preferred improvement of the present invention, in step S3, a polyacyl chloride monomer is dissolved in an organic solvent to obtain a polyacyl chloride solution; the polyacyl chloride monomer is an active acyl chloride monomer with difunctionality or above, the organic solvent is any one of n-hexane and cyclohexane, and the concentration of the polyacyl chloride solution is 0.01-0.5 mol / L.

[0015] As a preferred improvement of the present invention, the polyacyl chloride monomer is any one of trimesoyl chloride and terephthaloyl chloride.

[0016] As a preferred improvement of the present invention, in step S3, the phosphorus silicon composite material is placed in a polyacyl chloride solution for reaction for 30 seconds to 2 minutes, and then dried at low temperature to obtain an all-solid-state battery negative electrode material.

[0017] As a preferred improvement of the present invention, in step S3, the temperature of reacting the phosphorus silicon composite material in the polyacyl chloride solution is 20-60°C.

[0018] The beneficial effects of the present invention are as follows:

[0019] 1. The present invention mixes red phosphorus and nano-silicon and reacts the mixture with cyclodextrin, and uses the hollow structure of cyclodextrin to bind the nano-scale phosphorus-silicon mixture in its molecular cavity, thereby limiting the expansion of the negative electrode;

[0020] 2. The present invention further encapsulates the phosphorus silicon composite material inside the molecular cavity by reacting the phosphorus silicon composite material, i.e., cyclodextrin coated with the phosphorus silicon mixture, with a polyacyl chloride solution, thereby preventing the phosphorus silicon from diffusing out of the molecular cavity under pressure. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0023] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0024] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0025] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0026] The present invention provides a method for preparing an all-solid-state battery negative electrode material, comprising the following steps:

[0027] Step S1, weighing a certain mass of red phosphorus and nano-silicon and mixing them by ball milling to obtain a mixture;

[0028] Wherein, the mass ratio of the red phosphorus to the nano-silicon is 5-8:5-2.

[0029] Step S2, mixing the mixture with cyclodextrin by ball milling to obtain a phosphorus-silicon composite material;

[0030] Specifically, the mass proportion of cyclodextrin in the phosphorus silicon composite material is 0.5-5%.

[0031] Step S3, placing the phosphorus silicon composite material in a polyacyl chloride solution to react for a period of time, and then treating to obtain an all-solid-state battery negative electrode material. The polyacyl chloride solution is obtained by dissolving polyacyl chloride monomers in an organic solvent.

[0032] Specifically, the polyacyl chloride monomer is an active acyl chloride monomer with difunctionality or higher such as trimesoyl chloride and terephthaloyl chloride, the organic solvent is any one of n-hexane and cyclohexane, and the concentration of the polyacyl chloride solution is 0.01-0.5 mol / L.

[0033] In steps S1 and S2, the ball milling mixing rate is 200-500 rpm, the ball milling time is 15-60 min, and the ball-to-material ratio is 1:20-40.

[0034] Preferably, in step S3, the phosphorus silicon composite material is placed in a polyacyl chloride solution at a reaction temperature of 20-60° C. for reaction for 30 s-2 min, and then low-temperature drying is performed to obtain an all-solid-state battery negative electrode material.

[0035] The present invention is described in detail below through specific embodiments.

[0036] Example 1

[0037] (1) Weighing 90 wt% of red phosphorus (9 g) and 10 wt% of nano-silicon (1 g), and mixing them by medium-speed ball milling in a planetary ball mill to obtain a mixture; wherein the ball milling speed is 250 rpm, and the ball milling time is 30 min;

[0038] (2) weighing 0.2 g of cyclodextrin and adding it to the ball mill of the planetary ball mill in (1), and performing a secondary ball milling on the mixture and the cyclodextrin under the same parameters to obtain a phosphorus-silicon composite material;

[0039] (3) Dissolve trimesoyl chloride in n-hexane solvent to prepare a 0.15 mol / L polyacyl chloride solution, heat the reaction temperature to 30° C., then immerse the phosphorus silicon composite material prepared in (2) in the polyacyl chloride solution for reaction for 1 min, and dry at low temperature to obtain a negative electrode material for an all-solid-state battery.

[0040] Example 2

[0041] (1) Weighing 50 wt% of red phosphorus (5 g) and 50 wt% of nano-silicon (5 g), and mixing them by medium-speed ball milling in a planetary ball mill to obtain a mixture; wherein the ball milling speed is 250 rpm, and the ball milling time is 30 min;

[0042] (2) weighing 0.5 g of cyclodextrin and adding it to the ball milling tank of the planetary ball mill in (1), and subjecting the mixture and the cyclodextrin to a secondary ball milling under the same parameters to obtain a phosphorus-silicon composite material;

[0043] (3) Dissolving trimesoyl chloride in n-hexane solvent to prepare a 0.2 mol / L polyacyl chloride solution, heating the reaction temperature to 30° C., and then immersing the phosphorus silicon composite material prepared in (2) in the polyacyl chloride solution to react for 30 seconds. After low-temperature drying, a negative electrode material for an all-solid-state battery is obtained.

[0044] Example 3

[0045] (1) Weighing 10 wt% of red phosphorus (1 g) and 90 wt% of nano-silicon (9 g), and mixing them by medium-speed ball milling in a planetary ball mill to obtain a mixture; wherein the ball milling speed is 250 rpm, and the ball milling time is 30 min;

[0046] (2) weighing 0.5 g of cyclodextrin and adding it to the ball milling tank of the planetary ball mill in (1), and subjecting the mixture and the cyclodextrin to a secondary ball milling under the same parameters to obtain a phosphorus-silicon composite material;

[0047] (3) Dissolving trimesoyl chloride in n-hexane solvent to prepare a 0.2 mol / L polyacyl chloride solution, heating the reaction temperature to 30° C., and then immersing the phosphorus silicon composite material prepared in (2) in the polyacyl chloride solution to react for 30 seconds. After low-temperature drying, a negative electrode material for an all-solid-state battery is obtained.

[0048] The negative electrode materials prepared in Examples 1 to 3 were applied to an all-solid-state lithium battery and the performance of the all-solid-state lithium battery was tested, and the results are shown in Table 1. Specifically, the all-solid-state lithium battery includes a positive electrode, a negative electrode, and a sulfide electrolyte between the positive electrode and the negative electrode, the positive electrode is lithium nickel cobalt manganese oxide (NCM811), the sulfide electrolyte is Li6PS5Cl, and the negative electrode is prepared from the negative electrode material prepared in Example.

[0049] Table 1 All-solid-state lithium battery performance test results

[0050] First charge capacity (mAhg-1) First charge and discharge efficiency (%) Unmodified silicon anode 185 72 Example 1 215 81 Example 2 202 75 Example 3 208 78

[0051] From Table 1, it can be seen that the battery effects made with the modified silicon negative electrode are better than those of the battery including the unmodified silicon negative electrode.

[0052] The beneficial effects of the present invention are as follows:

[0053] 1. The present invention mixes red phosphorus and nano-silicon and reacts the mixture with cyclodextrin, and uses the hollow structure of cyclodextrin to bind the nano-scale phosphorus-silicon mixture in its molecular cavity, thereby limiting the expansion of the negative electrode;

[0054] 2. The present invention further encapsulates the phosphorus silicon composite material inside the molecular cavity by reacting the phosphorus silicon composite material, i.e., cyclodextrin coated with the phosphorus silicon mixture, with a polyacyl chloride solution, thereby preventing the phosphorus silicon from diffusing out of the molecular cavity under pressure.

[0055] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the embodiments. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing an all-solid-state battery negative electrode material, It is characterized in that The following steps are involved: Step S1, weighing a certain mass of red phosphorus and nano-silicon and mixing them by ball milling to obtain a mixture; Step S2, mixing the mixture with cyclodextrin by ball milling to obtain a phosphorus-silicon composite material; Step S3, placing the phosphorus silicon composite material into a polyacyl chloride solution to react for a period of time, and then treating it to obtain an all-solid-state battery negative electrode material.

2. A method for preparing an all-solid-state battery negative electrode material according to claim 1, It is characterized in that The mass ratio of the red phosphorus to the nano-silicon is 5-8:5-2.

3. The method for preparing a negative electrode material for an all-solid-state battery according to claim 1, It is characterized in that The mass proportion of cyclodextrin in the phosphorus silicon composite material is 0.5-5%.

4. The method for preparing a negative electrode material for an all-solid-state battery according to claim 1, It is characterized in that In steps S1 and S2, the ball milling mixing rate is 200-500 rpm, the ball milling time is 15-60 min, and the ball-to-material ratio is 1:20-40.

5. The method for preparing a negative electrode material for an all-solid-state battery according to claim 1, It is characterized in that In step S3, polyacyl chloride monomers are dissolved in an organic solvent to obtain a polyacyl chloride solution; the polyacyl chloride monomers are active acyl chloride monomers with difunctionality or higher, the organic solvent is any one of n-hexane and cyclohexane, and the concentration of the polyacyl chloride solution is 0.01-0.5 mol / L.

6. A method for preparing an all-solid-state battery negative electrode material according to claim 5, It is characterized in that The polyacyl chloride monomer is any one of trimesoyl chloride and terephthaloyl chloride.

7. The method for preparing a negative electrode material for an all-solid-state battery according to claim 1, It is characterized in that In step S3, the phosphorus silicon composite material is placed in a polyacyl chloride solution for reaction for 30 seconds to 2 minutes, and then dried at low temperature to obtain an all-solid-state battery negative electrode material.

8. The method for preparing an all-solid-state battery negative electrode material according to claim 1, It is characterized in that In step S3, the phosphorus silicon composite material is placed in the polyacyl chloride solution and the reaction temperature is 20-60°C.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery cathode material

    CN103296261A

  • Phosphor-doped silicon-graphite composite material, negative electrode material comprising same and lithium ion battery

    CN107240693A

  • Cyclodextrin directional arrangement ultrathin film and preparation method thereof

    CN118437165A

  • Methods for manufacturing SiP2 / C, anode material for composites SiP2 / C, and rechargeable battery comprising the same

    KR1020160027740A

  • Phosphorus-carbon cathode material based on red phosphorus and preparation method thereof

    US20240258523A1

Cited By

  • Phosphorus-doped porous carbon / silicon composite negative electrode material and preparation method thereof

    CN120809752A

  • Phosphorus-doped porous carbon / silicon composite negative electrode material and preparation method thereof

    CN120809752B

  • Black phosphorus-carbon-supramolecular composite material as well as preparation method and application thereof

    CN121149178A